Recent Publications (Quarterly Journal of Economics, 1941)
Journal Article Recent Publications Get access The Quarterly Journal of Economics, Volume 56, Issue 1_Part_1, November 1941, Pages 170–174, https://doi.org/10.1093/qje/56.1_Part_1.170 Published: 01 November 1941